2001
DOI: 10.1159/000050905
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfur Hexafluoride Gas on Antibacterial Activity of Antibiotics in vitro against Agents Causing Endophthalmitis

Abstract: Background: We conducted a study to evaluate the effect of sulfur hexafluoride gas (SF6) on the antibacterial activity of antibiotics in vitro against Staphylococcus aureus, Staphylococcus epidermidis and Pseudomonas aeruginosa, which are common endophthalmitis-causing agents. Methods: In this experimental study, antibiotic susceptibility tests were prepared according to the National Committee for Clinical Laboratory Standards macrobroth dilution method. Müller-Hinton broth was the test medium. Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The bioactive parts against bacteria in these conventional antibiotics include structural moieties that include-Cl,-F,-N,-NH 2, -S,-COOH and-OH, which are also found in many herbs used traditionally against bacterial infections. Studies have shown that sulfur-containing compounds have strong inhibitory antibacterial activities (Julia and Ann 1947;Kyung and Fleming 1996;Yanyali et al 2001). Nitrite exhibits toxic properties while nitrous acid is bactericidal, chlorine releasing compounds such as chlorine dioxide (ClO 2 ), acidic and alcoholic compounds act as antibacterial agents (Gerald and Russell 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive parts against bacteria in these conventional antibiotics include structural moieties that include-Cl,-F,-N,-NH 2, -S,-COOH and-OH, which are also found in many herbs used traditionally against bacterial infections. Studies have shown that sulfur-containing compounds have strong inhibitory antibacterial activities (Julia and Ann 1947;Kyung and Fleming 1996;Yanyali et al 2001). Nitrite exhibits toxic properties while nitrous acid is bactericidal, chlorine releasing compounds such as chlorine dioxide (ClO 2 ), acidic and alcoholic compounds act as antibacterial agents (Gerald and Russell 1999).…”
Section: Introductionmentioning
confidence: 99%